Competing Locations' Market Potential and FDI in Central and Eastern Europe vs the Mediterranean - Carlo Altomonte; Claudia Guagliano (Katholieke Universiteit Leuven, LICOS Centre for Transition Economics, 2001)
The issue of the location of Foreign Direct Investment is receiving a renewed interest in the literature since developing countries have now started to compete for the attraction of foreign capital. In particular, the European Union is at the centre of a region where strong integration dynamics are in place, and where the 'peripheries' i.e. Central and Eastern Europe and the South Mediterranean shore, are taking advantage of an increasing presence of European multinationals. The full implications of such dynamics, for both the European Union and the bordering countries, are yet to be fully understood given the complex issues behind the detfirminants of FDI location. At this purpose, we will exploit two unique databases, constructing a panel probit model of FDI detfirminants of more than 3,500 European multinationals having invested in Central and Eastern Europe and the Mediterranean over the 1990-1997 period in 48 NACE-3 different industries. We will then discuss the policy implications for the European Union and for its neighbouring countries of those FDI detfirminants.
Keywords: C23; F21; P20; 330; panel data; FDI; transition economies; Direktinvestition; Multinationales Unternehmen; Standortwettbewerb; Osteuropa; Nordafrika; Mittlerer Osten; Marktpotential